2017
DOI: 10.1126/sciadv.1601992
|View full text |Cite
|
Sign up to set email alerts
|

Pure iron grains are rare in the universe

Abstract: The extremely low sticking probability of iron inhibits the formation of metallic iron grains around evolved stars.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Rapid whisker growth as opposed to the formation of a protective iron shell implies that sulfides are easily destroyed under such conditions. Metallic iron is predicted to appear as a byproduct of this alteration process in the ISM and might exists there even though its primary formation by homogeneous nucleation from supernova ejecta appears to be highly ineffective 63 . Metallic iron in the ISM can be an important catalysts for molecule formation 64 and can produce magnetic dipole emissions that disturb the cosmic microwave background 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid whisker growth as opposed to the formation of a protective iron shell implies that sulfides are easily destroyed under such conditions. Metallic iron is predicted to appear as a byproduct of this alteration process in the ISM and might exists there even though its primary formation by homogeneous nucleation from supernova ejecta appears to be highly ineffective 63 . Metallic iron in the ISM can be an important catalysts for molecule formation 64 and can produce magnetic dipole emissions that disturb the cosmic microwave background 65 .…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the chemical binding of iron to interstellar dust particles is currently being debated. For example, from experiments in microgravity, Kimura et al (2017) concluded that the probability of the formation of pure iron grains should be very low and that, consequently, iron should be bound in iron compounds or accreted as impurities on other grains in the ISM. Another hypothesis was pursued by Bilalbegović et al (2016) who calculated infrared absorption spectra of hydrogenated iron particles.…”
Section: Comparison With Other Forms Of Ironmentioning
confidence: 99%
“…At a gas pressure of 4.0 × 10 4 Pa, the temperature of the nanoparticles is almost identical to that of the surrounding gas 19 . Owing to the reported temperature field around the evaporation source at 2226 ± 22 K under an Ar atmosphere of 4.0 × 10 4 Pa 20 , the nascent nucleated nanoparticles can retain a temperature of about 1000 K for a few seconds. This relatively long incubation time for the nucleation can induce the formation of α-Al 2 O 3 within the liquid-like particles under microgravity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the Al 2 O 3 nuclei have higher possibility to overcome a large barrier to form the most stable corundum phase. In addition, the slower cooling permits the gaseous atoms to collide more frequently and, on a longer timescale of gas cooling, provides a more realistic simulation of the grain formation in gas outflows from AGB stars 20 . Based on this concept, we performed an ideal-nucleation experiment in a microgravitational environment of 2.2 × 10 −3 m s −2 (2.2 × 10 −4 G) aboard the sounding rocket S-520 30 and successfully reproduce a 13 μm band with a very narrow width of 0.5–0.6 μm.…”
Section: Introductionmentioning
confidence: 99%